MANAGERIAL DISCOURSE IN FINANCIAL COMMUNICATION OF AN ALGERIAN PRIVATE COMPANY - Nezha Djellal Ameur1*; Soraya Hamane2 (Chelonian Research Foundation, 2023)
This study investigates the corporate communication practices in an Algerian firm from 2019 to 2023. The research concentrates explicitly on the language subtleties seen in the presentation letters accompanying the yearly financial statements produced by the management. This study aims to comprehend the many persuasive strategies employed without digging into the later ramifications that may arise. This study utilises a cross-sectional approach to examine the interplay between language, culture, and the depiction of reality. This study highlights the significance of social and discursive environments in influencing communication, explicitly focusing on factors such as the author’s identity, the intended audience, and the interconnections between them. The present study also examines the form of argumentation in financial communication, providing insights into the interpretive frameworks of speakers operating within the corporate environment of Algeria. The importance of good communication in promoting commitment and demonstrating social responsibility is emphasised. Algerian firms employ various communication tactics to effectively communicate their contributions to the nation’s development and navigate enterprise’s expectations. This study provides significant insights into the changing financial communication techniques firms employ in Algeria. Keywords: Corporate Communication, Linguistic Nuances. Financial Discourse. Social Responsibility. Algerian Enterprise